Respuesta :

Wolfyy

Hey!

------------------------------------------------

Steps To Solve:

0.61m - 1.51m = 9

~Combine Like Terms

-0.9m = 9

~Divide -0.9 To Both Sides

-0.9m/-0.9 = 9/-0.9

~Simplify

m = -10

------------------------------------------------

Hence, m equals -10!

------------------------------------------------

Hope This Helped! Good Luck!

Answer and Step-by-step explanation:

[tex]\huge\boxed{~~m=-10~~}[/tex]

Step 1: Simplify both sides of the equation:

[tex]=0.61m+-1.51m=9[/tex]

[tex]=(0.61m+-1.51m)=9[/tex]          (Combine the like terms)

[tex]=-0.9m=9[/tex]

Step 2: Divide both sides by -0.9:

[tex]\frac{-0.9m}{-0.9} =\frac{9}{-0.9}[/tex]

[tex]m=-10[/tex]

Thus, the answer is "m = -10"

ACCESS MORE